Design and Development of an Artificial Intelligence - Supported Educational Portal with Role-Based Authorization Structure - Karabatak, Songul; Alanoglu, Muslim; Karabatak, Murat; Basatoǧrul, Beyza (Institute of Electrical and Electronics Engineers Inc., 2026)
This study addresses the design and development process of an artificial intelligence-supported educational portal with a role-based authorization structure, aimed at reducing the adaptation challenges and experiences referred to as 'reality shock' encountered by pre-service teachers during their transition into the teaching profession. The study was conducted within the scope of the TÜBITAK 1001 research program as part of the project titled 'Design of an Instruction Supported by a Digital Assistant for Pre-service Teachers to Overcome Reality Shock and Investigation of its Effectiveness' (Project No. 323K013). The research was carried out as a design- and development-oriented system development study. Accordingly, the web-based educational portal was structured around three primary user roles: Admin, Advisor, and Student. This paper presents a detailed overview of the portal's role-based authorization model, the functions of user panels, and the integration and positioning of the AI-supported digital assistant within the system. The development of the portal is ongoing, and following the completion of the development process, an experimental implementation and evaluation phase is planned to examine the effectiveness of the portal. © 2026 IEEE.
14th International Symposium on Digital Forensics and Security, ISDFS 2026 -- 19 March 2026 through 20 March 2026 -- Boston -- 222184
Keywords: Ai-Supported Educational Portal; Design And Development; Role-Based Authorization